(untitled) (Health Renaissance, 2011)
Background: Convergence insufficiency (CI) is a common ocular morbidity encountered in clinical optometry practice. It decreases the efficacy for near work. Pencil push up therapy (PPT) is frequently used for the treatment of CI. Aim: The aim of the study was to determine the effectiveness of pencil push up exercise in convergence insufficiency patients. Methods: A hospital based interventional longitudinal prospective study was designed. All patients attending BP Koirala Lions Centre of Ophthalmic Studies (BPKLCOS), Nepal from March 1st 2008 to February 28, 2009 with symptomatic convergence insufficiency were included in this study. Near point of convergence (NPC), prism fusion vergence (PFV) and symptom score were measured with RAF ruler, prism bar and symptom questionnaire respectively before and after PPT. Results: Out of 84 patients included in the study, only 23 completed follow up check up. Among them 73% were female and 23% were male. The mean age of patients was 19.93±6.0 years and 73% of the total were students. The improvement in NPC was statistically significant after PPT (p =0.008). The average NPC at first visit was 18.58±7.46 cm while at follow up visit, it was 11±4.6 cm. The PFV and average symptom score were also improved significantly. Conclusion: PPT is beneficial for CI patients. It improves the NPC, PFV and reduces the symptom of the patients. However, the compliance of Nepalese CI patients with PPT is poor. Keywords: NPC; PFV; convergence insufficiency; pencil push up therapy. DOI: http://dx.doi.org/10.3126/hren.v9i3.5583 HR 2011; 9(3): 157-161